The Use of Neuroscience and Psychological Measurement in England's Court of Protection - McWilliams, Andrew; Fleming, Stephen M.; David, Anthony S.; Owen, Gareth (Frontiers in Psychiatry, 2020)
The 2005 Mental Capacity Act of England and Wales provides a description in statute law of a test determining if a person lacks “mental capacity” to take a particular decision and describes how the “best interests” of such a person should be determined. The Act established a new Court of Protection (CoP) to hear cases related to the Act and to rule on disputes over mental capacity. The court gathers a range of evidence, including reports from clinicians and experts. Human rights organisations and others have raised concerns about the nature of assessments for incapacity, including the role of brain investigations and psychometric tests. Aim: Describe use and interpretation of structured measures of psychological and brain function in CoP cases, to facilitate standardisation and improvement of practices, both in the courtroom and in non-legal settings. Method: Quantitative review of case law using all CoP judgments published until 2019. The judgments (n=408) were read to generate a subset referring to structured testing (n=50). These were then examined in detail to extract the nature of the measurements, circumstances of their use and features of interpretation by the court. Results: The 408 judgments contained 146 references to structured measurement of psychological or brain function, spread over 50 cases. 120/146 (82.2%) referred to ‘impairment of mind or brain’, with this being part of assessment for incapacity in 58/146 (39.7%). Measurement referred on 25/146 (17.1%) occasions to ‘functional decision-making abilities’. Structured measures were used most commonly by psychiatrists and psychologists. Psychological measurements comprised 66.4% of measures. Neuroimaging and electrophysiology were presented for diagnostic purposes only. A small number of behavioural measures were used for people with disorders of consciousness. When assessing incapacity, IQ and the Mini-Mental-State Examination were the commonest measures. A standardised measure of mental capacity itself was employed just once. Judges rarely integrated measurements in their capacity determinations. Conclusion: Structured testing of brain and psychological function is used in limited ways in the Court of Protection. Whilst there are challenges in creating measures of capacity, we highlight an opportunity for the neuroscience community to improve objectivity in assessment, inside and outside the courtroom.